Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1039/c6ra14152h
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and charge transfer properties of organic BODIPY dyes integrated in TiO2nanotube based dye-sensitized solar cells

Abstract: A BODIPY dye grafted on TiO2 NTs is fully characterized and applied in dye-sensitized solar cells showing a good performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 66 publications
(34 reference statements)
1
18
0
Order By: Relevance
“…(4) Synthesis of vertically aligned TiO 2 -NTs on the microcantilevers was done by electrochemical anodization of the metallic Ti layers. This method has been reported in a previous work 30 and modified here in order to obtain dense, open and oriented TiO 2 -NTs on both sides without any damage on microcantilever (e.g. dissolution of silicon).…”
Section: Resultsmentioning
confidence: 99%
“…(4) Synthesis of vertically aligned TiO 2 -NTs on the microcantilevers was done by electrochemical anodization of the metallic Ti layers. This method has been reported in a previous work 30 and modified here in order to obtain dense, open and oriented TiO 2 -NTs on both sides without any damage on microcantilever (e.g. dissolution of silicon).…”
Section: Resultsmentioning
confidence: 99%
“…When dyes 18 and 19 are used as cosensitizers, both the photocurrent and voltage increased, resulting in an impressive PCE of 6.43%, which is the best reported so far for BODIPY-sensitized solar cells. In another study, Gonzalez-Valls and coworkers further introduced polyethylene to the styryl functionalized legs and prepared dye 21 with the benzoic acid as an anchoring group and prepared for TiO 2 nanotube-based solar cells. It was found that the dye 21 adsorbed 100 times less than ruthenium dye N3.…”
Section: Bodipy Dyes For Dye-sensitized Solar Cellsmentioning
confidence: 99%
“…1b). 13,16 In other instances, the 3,5 positions of the pyrrole rings are functionalized with linkers and anchoring groups for surface attachment (Fig. 1c).…”
Section: Introductionmentioning
confidence: 99%